Technetium-99m-Labeled Diethylcarbamazine Citrate (99mTc-DEC) as a New Diagnostic Agent for Lymphatic Filariasis Detection - N. K. Oekar; A. Hanafiah; D. Setiawan; E.M. Widyasari (Atom Indonesia, 2017)
Lymphatic filariasis or more commonly known as elephantiasis disease has infected more than 120 million people in 80 countries; and more than 40 million of them are unable to work, in addition to disruption of aesthetic values. The problem faced by almost all people in combating this infectious disease is delayed diagnosis. The sufferers do not realize that they have been infected with this disease. A specific and accurate method of early detection is therefore needed. 99mTc-labeled Diethylcarbamazine-citrate (99mTc-DEC) has been successfully prepared. However, as part of the discovery and development of new drugs, the fulfillment of pharmaceutical and safety requirements have to be evaluated. Physico-chemical aspects such as stability, purity levels, and other pharmaceutical requirements, as well as pharmacokinetic studies and route of administration, are important parameters to be studied. The stability test showed that after seven months of storage, a preparation in a dry kit retains an efficiency of labeling and a purity level of more than 90 % and its physico-chemical and biological characteristics remained steady. Biodistribution test in Wistar rat showed that the greatest accumulation occurred in the lymphatic system, especially in the popliteal glands and in lumbar and mesenteric lymph nodes. Imaging with a gamma camera after intradermal and intravenous injections to the experimental animals resulted in a positive image that showed 99mTc-DEC accumulation in the target organ. The results of this innovation are expected to contribute significantly to improving public health, particulary in early detection of filarial infections. In addition, this result is expected to be a concrete contribution to the program of "The Global Goal of Elimination of Lymphatic Filariasis as a Public Health Problem by the Year 2020”.